Mnemonic Learning in Increasing Early Children's Arabic Vocabulary - Umar Manshur; Fathor Rozi; Tutik Umi Athiyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to find out how the form of applying mnemonic learning in increasing Arabic vocabulary in early childhood at RA Darussalam, Prasi, Gading. This research used a qualitative approach with a type of field research. The data sources were obtained through 2 research instruments, namely observation, interviews, and documentation with 5 informants (principals, homeroom teachers for classes A and B, and 2 student guardians). The data analysis technique used the Miles and Huberman Interactive Model with data reduction activities, data presentation, and drawing conclusions. Data validity with source and technique triangulation process. Learning Arabic using the mnemonic method as an effort to increase students' Arabic vocabulary was accomplished by several activities. Among them were the introduction of hijaiyah letters and their punctuation, choosing material sources according to student needs, recognizing and repeating the rhythm of the song, providing learning concepts with mind maps, and reflecting on learning experiences into new knowledge for students. This mnemonic learning becomed a remembering strategy for students by involving the right brain so that information will be stored longer and easier to recall when needed because it is stored in long-term memory.